Myths About Breastfeeding as Voiced by Lactating Nurses and Midwives: A Qualitative Study at the Greater Accra Region of Ghana - Angela Kwartemaa Acheampong PhD, MPhil, PGDE, BSc, RN; Alhassan Sibdow Abukari PhD, MPhil, BSc, Dip, RN (SAGE Publishing, 2024)
Introduction Breastfeeding has proven over the years to be one of the most effective means to ensure child survival. The advocators and myth busters of breastfeeding myths are supposed to be health professionals. However very little is known about myths surrounding breastfeeding as expressed by these health professionals (nurses and midwives). Hence this study. Objective The study aimed at exploring the myths about breastfeeding as voiced by lactating nurses and midwives. Method Qualitative exploratory descriptive design was used to investigate the subject matter. Twenty-five nurses and midwives were purposely selected to participate in the study after they had voluntarily opted to be part of the study. Data was audiotaped, transcribed verbatim and inductively analyzed. Results It was evident that participants believed in myths about breastfeeding. The main themes discovered were breastfeeding myth beliefs and sociocultural myth influences. Six sub-themes identified were green stools/diarrhoea, childhood disease, teeth discoloration, child becoming stupid, culture and close relatives. Conclusion Health professionals believe in unfounded myths about breastfeeding. Steps should be taken for them to get better lactation support. The outcomes of this study underscore the need for health professionals to address breastfeeding myths, understand the sociocultural context, and support evidence-based practice. Improving lactation support and education for nurses and midwives can lead to better clinical practice and, as a result, help to promote successful and healthy breastfeeding in Ghana.